ROLE OF SEMANTICS WEB TECHNOLOGIES IN REDUCE TIME COMPLEX HETEROGENEOUS INFRASTRUCTURES - Pandey, Sachin Kumar; Pandey, Prabhat (International Journal of Computer Sciences and Engineering, 2025)
During today’s period about current information technology, great amount about information be produced each next toward allow succeeding information aggregation moreover psychiatry. but, the IT infrastructures to contain element set awake more than previous little decades also ought near currently be used designed for it principle be awfully heterogeneous also complex. Because result, tasks used for scrutinizing information, such because gathering, searching, kinds also giving out information grow to be extremely time-consuming. It creates difficult near recognized revelation, such like Internet about making, which follow the objective about declaration the ease of use about concurrent information on several time also set in an business location. Near decrease the time just before analytics in such location, we near a information eating, combination also giving out proceed consisting about a flexible also configurable information eating pipeline as well as a dynamic semantic information period name ESKAPE. The major objective be, consequently, the convenient right of entry to information also Meta information enclosed inside machines moreover additional systems lying on the superstore. Moreover, it provides the opportunity near onward the together information near a configurable endpoint, such information mere. ESKAPE acts like individual about person's endpoints enable dynamic semantic information incorporation also processing. Near explain information sets by dynamic semantic models initiated as of the Semantic Web, information analyst be clever near realized procedure also find out these information sets additional competently. ESKAPE skin a three or more - layered information storage structural design consisting about an information layer intended for accumulated included untreated information sets, a layer included user-defined semantic models near illustrated the relative acquaintance required near understand the accumulated information also a top layer bent by a incessantly developing acquaintance graph, unite semantic